Changes of Gut Microbiota and Its Correlation With Short Chain Fatty Acids and Bioamine in Piglets at the Early Growth Stage - Qi, Renli; Qiu, Xiaoyu; Du, Lei; Wang, Jing; Wang, Qi; Huang, Jinxiu; Liu, Zuohua (Frontiers in Veterinary Science, 2021)
The change characteristics of intestinal microbial succession and the correlation with the production of two important types of bacterial metabolites (short chain fatty acids and bioamine) in piglets during the early stage were fully explored in this study. Six piglets from different litters with the same birth time were selected, weighted and euthanized at 1, 7, 14, 21, 28, 35 and 42 days of age. During this stage, the piglets grew quickly with gradual increases in blood levels of growth hormone and insulin, and in the intestinal developmental index and immunity. 16s rRNA analysis indicated the alpha diversity of colonic microbiome community was higher than ileum. However, the composition change in the ileal microbiota was more dramatic over time. Lactobacillus genus was the dominant bacteria in piglets’ ileum while Prevotella and Ruminococcaceae genera were the dominant bacteria in colon up to weaning. Gut bacterial community of the piglets showed obvious differences between the three different phases: newborn, before weaning, and post weaning. This was similar to the morphological change pattern of pigs’ gut. Total SCFA content in the colon of pigs showed almost a 20-fold increase at day 42 compared to the value at day 1. The percentage of acetic acid among the total SCFAs dropped quickly from 74.5% at day 1 to 36.5% at day 42, while butyric acid and propionic acid showed significant increases at the stage. The histamine level increased and putrescine level decreased markedly in the colon with time while the amounts of total bioamines, tyramine and spermidine were devoid of changes. Dozens bacteria taxa showed highly correlations with SCFAs and bioamines. These findings provide an expanded view of the dynamic pig gut and gut microbiome at the important early growth stage.